HUBUNGAN KARAKTERISTIK SOSIODEMOGRAFI DAN PANJANG BADAN LAHIR DENGAN KEJADIAN STUNTING PADA BADUTA USIA 6 – 24 BULAN DI KOTA DENPASAR - Vernanda Sofyantira, Hanifrida; Sutiari, Ni Ketut (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024, 2025)
Stunting is a disorder of growth and development of children due to chronic malnutrition and repeated infections, which are characterized by their length or height being below standard. Stunting is influenced by sociodemographics, pregnant women, toddlers' diet, and the economy. Stunting in Indonesia has a prevalence of 36% or as many as 8.8 million toddlers. The purpose of this study was to determine the relationship between sociodemographic characteristics and birth length with the incidence of stunting in toddlers aged 6-24 months in Denpasar City. This research is an observational study with a cross sectional design. This research was carried out in several working areas of activities. Researchers conducted interviews with mothers of toddlers, using questionnaires, and the data will be processed and analyzed with SPSS software version 26.0. The results obtained are that there is a relationship between maternal age during pregnancy and birth length status with the incidence of stunting in toddlers aged 6-24 months in Denpasar City. Parents are expected to pay attention to the nutrition of their children, especially for children born with short birth length so they don't experience stunting as toddlers. Counseling is needed for pregnant women and mothers with toddlers about the causes of stunting at the puskesmas.. Keywords : Stunting, Birth Length, Baduta